Balance Performance in Adolescents Following a Concussion - Rochefort, Coralie (Université d'Ottawa / University of Ottawa, 2019)
A concussion can result in a wide range of signs and symptoms including physical, cognitive, emotional and sleep-related symptoms. While a concussion can occur at any age, children and adolescents are at an increased risk of experiencing a concussion. Important physical consequences of concussion are balance deficits which affect approximately one in three cases. Balance is essential to perform many postures and activities and therefore it is important to accurately identify these deficits at the time of injury and during the recovery process in order to avoid potential further injury. A review of the literature regarding the different clinical and laboratory measures used to assess balance following a concussion was completed and identified several gaps in the literature. The four studies in this thesis were tailored to address these gaps in knowledge. The first study addressed the sensitivity of a gold standard clinical measure and laboratory measures of standing balance in terms of identifying balance deficits in adolescents at 1-month post-concussion. Performance on the Balance Error Scoring System (BESS) and COP measures from single and dual-task balance conditions were compared between a group of adolescents at one-month post-concussion and a group of non-injured adolescents. The results demonstrated that COP measures from single and dual-task conditions identified balance deficits in the concussed group that were not captured by the BESS. The second study addressed whether self-reported balance problems are a suitable alternative to COP measures to identify balance deficits in concussed adolescents. A secondary analysis of the data from study 1 was conducted to compare COP measures from the single and dual-task conditions between concussed adolescents self-reporting balance problems, concussed adolescents self-reporting no balance problems and a group of non-injured adolescents. The results from this analysis showed that the concussed adolescents demonstrated balance deficits regardless of whether they self-reported balance problems. There is significant clinical interest that lies in the ability to predict which adolescents presenting in the emergency department with concussion will be affected with ongoing balance deficits. The third study addressed the predictive ability of a set of COP variables recorded within the first 10 days following injury in a group of concussed adolescents to predict balance performance on a dual-task condition at one-month post-injury. Seven COP variables were identified as significant predictors. A secondary objective of this study was to compare performance on the COP measures between the concussed adolescents and a group of non-injured adolescents during the first session within the first 10 days following injury and during the second session at one-month post-injury and to compare performance between sessions within each group. The between session comparisons showed that performance remained relatively stable across sessions within both groups. In contrast, the between group comparisons revealed several significant differences in COP measures between the concussed and non-injured groups. The fourth study in this thesis addressed the association between balance and saccadic eye movements in concussed adolescents. Impaired saccadic eye movements are an important consequence of concussion and may be associated with balance deficits since both processes are dependent on several of the same cortical structures and brainstem areas. In this study, concussed and non-injured adolescents performed three different dual-task balance conditions involving either a high cognitive load, a low cognitive load and a gaze shifting component or a high cognitive load and a gaze shifting component. The results demonstrated that the concussed adolescents swayed over larger 95% ellipse areas while performing the two dual-tasks with the gaze shifting component, but these larger amounts of sway were not associated with an increase in saccades. Taken together, these four studies extend the current knowledge regarding balance performance in concussed adolescents and provide results that can be applied to balance assessments for concussion.
Keywords: Concussion; Balance; Adolescents; Center of Pressure; Saccades; Eye Tracking